Pembuatan Gula Aren Cair dengan Pengaturan Kapur dan Suhu Evaporasi - Didik Nursafuan; Ersan Ersan; Dedi Supriyatdi (Jurnal Agro Industri Perkebunan, 2016)
National sugar requirement for direct consumption of households and industry will increase in line with population growth. The national sugar demand in 2014 reached 5,700 million tons, while national production only 3,500 million tons. The aim of research to get a way to make palm sugar liquid.Â  With a temperature of line and evaporation. The research was arranged in a randomized complete block design with a factorial treatment without the provision of lime and lime 0,05% combined with avaporation temperature of 70 0C, 80 0C, evaporation temperature and 90 0C, evaporation temperature. The result showed that the best result of tained in the treatment of lime with evaporation temperature of 70 C ocontent % feces 0,49,043% ash content, reduction sugar 3,75% All treatment SNI of lime meet the quality standards.Keywords: evaporation temperature, lime, liquid palm sugarPermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/49